Antioxidant, Tyrosinase Inhibition Activity, and In Vitro SPF Evaluation of Pepino Fruit Extract (Solanum muricatum Aiton) in Different Solvent Types and Concentrations - Sugihartini, Nining; Firsty, Girly Risma; Laila, Wahyu Kumil; Mulyaningsih, Sri; Rais, Ichwan Ridwan (Pharmaceutical Sciences and Research, 2024)
Solvent is a key factor that affects the effectiveness of active compound extraction from plant materials (simplisia). This study aimed to determine the optimal type and concentration of solvent used in the extraction of pepino fruit based on the parameter of antioxidant and tyrosinase inhibition activity, as well as Sun Protection Factor (SPF) value. The extraction was carried out using the maceration method with ethanol or ethyl acetate as the solvent, each at concentrations of 50%, 70%, and 96%, respectively. The antioxidant activity of the extracts was evaluated using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method. The inhibition of tyrosinase and the determination of the SPF value were carried out using in vitro test. The results showed that the ethyl acetate extract was better than that of the ethanol extract in terms of antioxidant activity, tyrosinase inhibition, and SPF value. In the ethyl acetate solvent, a concentration of 96% provided the strongest antioxidant, tyrosinase inhibition activity, and the second highest in SPF test. It can be concluded that the optimal solvent for extracting pepino fruit as promising compound for sunscreen formulation is 96% ethyl acetate.